(untitled) (Annals of Medical Research, 2021)
Aim: To discuss the natural history of spinal meningiomas (SMs) in our series, surgical approach options, and pathology results in light of the literature. Material and Methods: Of the 151 meningioma cases operated on between June 2014 and August 2020 in our center, 11 with spinal localization were analyzed retrospectively. Results: Three (27%) of our cases were male, eight (73%) were female, and 7.2% of all meningioma cases were located in the spine. The patients mostly presented with paraparesis, and 73% of the tumors had a thoracic localization and 64% had a lateral spinal localization. We were able to reach a 90% Simpson grade I resection limit after the opening procedure performed with mostly hemilaminectomy or laminoplasty. The histopathologies of all our cases were reported as meningothelial and transitionally weighted WHO grade I, and their postoperative clinical states showed a favorable progression according to the Karnofsky and McCormick scales. Conclusion: WHO grade I histopathology and thoracic spinal location are predominant in SMs. With low recurrence and mortality rates, favorable outcomes can be obtained with gross total resection in most cases. Due to the slow course of SMs, care should be taken against the possibility of misdiagnosis.